Marketing As A Mediator Variable For Human Resources To The Performance Of Agroprenerur MSMES - Prakoso; Agung Suryo; Sudarmiatin; Hermawan; Agus (CV. AFDIFAL MAJU BERKAH, 2022)
The purpose of this study is to analyze the influence of human resources on the performance marketing of micro, small and medium enterprises (MSMEs). This study was conducted on MSME Agropreneurs in Cikarang Regency, West Java. The analysis method used is Path Analysis. This study used explanatory research. The research population is all agropreneur MSME actors. This study used a Likert questionnaire given to 69 business actors. The results showed that Human Resources have a positive effect on marketing. Research also shows that marketing has a positive effect on the performance of MSMEs. Human resources and marketing together is an effective consideration for management in order to achieve small medium Enterprise performance.